Features of GERD therapy in obese patients: A review - Natalia V. Bakulina; Sergey V. Tikhonov; Anastasia Yu. Efremova; Vakhtang V. Mirtskhulava (ZAO "Consilium Medicum", 2023)
Epidemiological, endoscopic and pathophysiological studies confirm the relationship between obesity and gastroesophageal reflux disease (GERD) and is characterized by a more severe course, has clinical and pathophysiological features. In the treatment of GERD, it is necessary to use an individualized integrated approach, which consists in the combined use of diet therapy, lifestyle changes and drug therapy. The basis of pharmacotherapy for GERD are proton-pump inhibitors that positively affect the quality of life and long-term prognosis. At the same time, pharmacodynamic and pharmacokinetic features determine the advantage of the rabeprazole molecule in obese patients, including the minimal risk of drug-drug interactions.